The Influence of Celebrity Endorsers, Product Knowledge And Brand Image on Gen Z's Purchase Decisions on Skintific Products: Marketing, Skincare - Alifia, Frasyla Putri Alifia; Huda, Achmad Syamsul (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of celebrity endorsers, product knowledge, and brand image on purchasing decisions for Skintific products among Generation Z in Jabodetabek. With the increasing awareness of the importance of skin care and the development of the beauty industry, Skintific has become one of the popular brands in Indonesia. The research method used is a quantitative approach with data collection through questionnaires distributed to 160 respondents. The results of the regression analysis show that celebrity endorsers, product knowledge, and brand image have a positive and significant influence on purchasing decisions. Simultaneously, the three variables explain 62% of the variation in purchasing decisions. These findings indicate that marketing strategies involving influencers and good product knowledge can increase consumer purchasing interest, as well as the importance of building a strong brand image to attract the attention of Generation Z. This study is expected to provide insight for manufacturers in designing more effective marketing strategies in the digital era. Keywords: Celebrity Endorser, Product Knowledge, Brand Image, Purchasing Decision, Generation Z, Skintific.